Disability, politics and culture in Kosovo - Krasniqi, Vjollca (Socialno delo, 2014)
The article focuses on social policy, politics and cultural representations ofdisability in post-war and post-independence (2008) Kosovo. It recounts the living conditions of people with disabilities that continue to be harsh as they face multiple levels of exclusion and oppression, stigmatisation, and violence. Seeking to understand agency, the article analyses the relationship between the state and disability movement. It also explores the ways in which disability, as an embodied condition and a form of social identity, functions in the cultural imagination and systems of representation. Three specific points will be made. First, the article seeks to show that the legislative instruments concerning disability ensure de jure but not de facto equality.The existing legal model of disability has not eased the social divisions and inequalities in the broader social structure in Kosovo. Second, it explains how participation of the disability movement in the political processes in general, and social policy formation in particular, has challenged the hierarchical 'social geography' and opposed the ideologies of ableism. Third, disability as an embodied condition and a form of social identity in the cultural imagination is predominantly that of an abject body. The categories of the body dominant in discursive representations are those of physically disabled and war-induced disabilities, rendering other types of disabilities invisible. The article will show how the body politic as well as social, economic, and cultural discourses and formations in Kosovo are premised on a binary matrix of the abled and disabled body and identities.
Keywords: telo; hendikep; identiteta; zastopništvo; reprezentacija; politics; politika; culture; kultura; Kosovo